Pelatihan Bermain Kata dalam Meningkatkan Kecerdasan Linguistic pada Siswa Kelas III SDN Putat Kidul 02 Malang - Arief Rahman Hakim (ADIMAS Jurnal Pengabdian Kepada Masyarakat, 2019)
Playing is one way to develop students' linguistic intelligence. Well-designed play will make students unconsciously learn. Students can be active, volunteer, without coercion. This devotion program is in the form of word play training on third grade students of SDN Putat Kidul 02 Gondanglegi Kabupaten Malang".  Methods in this devotion use a practice approach that consists of games or games that include aspects of cognitive, affective and psychomotor. This activity is intended to develop students' linguistic intelligence to have the ability to use words effectively, both orally and in writing using the operational core of the language clearly to express and appreciate complex meanings. The results of training in developing linguistic intelligence for third grade students SDN Putat Kidul 02 Gondanglegi Kabupaten Malang have a positive impact. The results of the activity indicate that there are direct or indirect changes in the students' ability during the learning process in using the word effectively, orally in language skills through student interaction.